2013
DOI: 10.4161/viru.27023
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms

Abstract: Our understanding of the virulence and pathogenesis of Francisella spp. has significantly advanced in recent years, including a new understanding that this organism can form biofilms. What is known so far about Francisella spp. biofilms is summarized here and future research questions are suggested. The molecular basis of biofilm production has begun to be studied, especially the role of extracellular carbohydrates and capsule, quorum sensing and two-component signaling systems. Further work has explored the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 145 publications
(242 reference statements)
1
42
0
Order By: Relevance
“…Likewise, the relation between bacterial biofilm formation and OMVs is a well-recognized biofilm component found in several microorganisms, including Francisella spp. [55], P. aeruginosa [56], and H. pylori [57]. Indeed, H. pylori OMVs importantly participate in extracellular matrix formation in strain TK1402 biofilms [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the relation between bacterial biofilm formation and OMVs is a well-recognized biofilm component found in several microorganisms, including Francisella spp. [55], P. aeruginosa [56], and H. pylori [57]. Indeed, H. pylori OMVs importantly participate in extracellular matrix formation in strain TK1402 biofilms [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of biofilms in infectious diseases [5][6][7][8][9][10], the regulation of Francisella biofilm assembly was investigated and led to identifying the Sec secretion system [3] as well as of the transcription factor qseB [11] as main players of the biofilm regulatory cascade [12]. Although not demonstrated experimentally, and considering the role of Francisella chitinases in biofilm formation, it has been hypothesized that biofilms would significantly contribute to Francisella persistence in both aquatic habitats and mosquito hosting vectors [3,13,14]. The correlation between Francisella biofilm dispersion and an increased bacterial susceptibility towards biocides has been reported [14,15] and we have recently brought first genetic evidence that the biofilm growth mode provides F. tularensis with a reduced susceptibility towards fluoroquinolones [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, following research revealed that the MVs themselves are actually incorporated in the biofilm matrix (Schooling and Beveridge, 2006). This was seen in Francisella biofilms as well (van Hoek, 2013). He et al (2017He et al ( , 2019 discovered that MV secretion in methicillin-resistant S. aureus (MRSA) was correlated with biofilm formation during improper vancomycin chemotherapy.…”
Section: Mvs In Biofilmmentioning
confidence: 99%
“…A vaccine based on detergent-extracted OMVs originating from the pathogenic bacterium Neisseria meningitides, complemented with recombinant proteins, has recently been approved and used to protect people against meningitis B. Several traits, such as the overexpression of certain antigens or the modification of the LPS reactogenicity, can be altered by genetically engineering the OMV-producing bacteria to yield a vaccine that meets the specific needs (van der Pol et al, 2015). Furthermore, active immunization of mice with P. aeruginosa MVs resulted in mice that were protected from P. aeruginosa infections (Zhang et al, 2018).…”
Section: Immunomodulatory Effects Of Mvsmentioning
confidence: 99%